Keanekaragaman Arthropoda pada Tanaman Sawo (Manilkara zapota) di Universitas Sriwijaya Kampus Indralaya - Artika, Aziza; Irsan, Chandra; Dwiyanti, Hana; Khabibah, Nuril; Agustin, Selvia; Syabella, Tantri; Agustin, Hera (Seminar Nasional Lahan Suboptimal, 2024)
Artika, A., Irsan, C., Dwiyanti, H., Khabibah, N., Agustin, S., Syabella, T., Agustin, H. (2024). Diversity of Arthropod in sawo plants (Manilkara zapota) at the campus of Universitas Sriwijaya Indralaya. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang  21 Oktober 2024. (pp. 731–742).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).There are many factors that prevent Indonesia from exporting mustard fruits to other countries, one of which is that mustard fruits spoil quickly. Mustard fruit is an agricultural product that cannot be stored for a long time, so it is at high risk in marketing. This field practice aimed to identify insect species found on mustard fruit in the ATC (Agriculture Training Center) field and in places overgrown with mustard fruit inside the Sriwijaya University Indralaya campus. This field practice uses direct survey methods and insect identification using the Google Picture Insect application. The results showed that 4 different orders and 7 different families were found. The insect orders are Diptera, Hemiptera, Hymenoptera, and Lepidoptera. For the Diptera order, 2 families were found, namely D. melanogaster from the Drosophilidae family and B. dorsalis from the Tephritidae family. The Lepidoptera order also found 2 families, namely O. subnotata from the Erebidae family and L. omnivora from the Psychidae family. As for the other 3 orders, each insect order only found one family. Of all the insects identified, C. pennsylvanicus and P. manihot were the two most common insect species found on the three observed sawo plants. The number of fruit flies found on sawo plants was 83, the intensity of attack on sawo fruits was up to 29.61%. Based on the results found there are 7 species of insects and 1 species of spiders that are found to live in mustard plants. The 7 insect species are Drosophila melanogaster, Bactrocera dorsalis, Phenacoccus manihot, Tartessus ferrugineus, Camponotus pennsylvanicus, Orvasca subnotata, Liothula Omnivora, and the spider species found is Telemonia dimidiate. The ant species Camponotus pennsylvanicus can be found in all parts of the sawo plant. Insect species in the ATC field included B. dorsalis, P. manihot, C. pennsylvanicus, and O. subnotata. And one spider species found in the ATC field is the spider species T. dimidiata. Meanwhile, at least 3 insect species were found in fisip fruit plantations. Insect species found in fisip fruit plantations are D. melanogster, T. ferrugineus, and L. omnivora.